PEMANTAUAN GULA DARAH MANDIRI DIMASA PANDEMIC COVID 19 PADA PASIEN DIABETES MILITUS ANGGOTA PERSADIA KOTA SEMARANG - Nur Anna Chalimah Sa'dyah; Farroh Bintang Sabiti (Jurnal Bakti untuk Negeri, 2022)
People with diabetes who join the Indonesian Diabetes Association (PERSADIA) Semarang have around 150 members and many activities are carried out with the aim of controlling the condition of disease disorders due to Diabetes Mellitus (DM), activities in the form of joint gymnastics and training activities. Since the COVID19 pandemic occurred, all activities havebeen stopped because people with DM are a vulnerable population to be affected by COVID. Many DM sufferers even contracted COVID and had to do ISOMAN so they were constrained not being able to do a blood glucose examination. Purpose: to provide knowledge and monitoring blood glucose levels using a glucometer so can increase knowledge by practicing at home. Implementation are data collection of PERSADIA members, preparation of materials, implementation and documentation of activities and reports. The material presented is monitoring blood glucose levels independently with a glucometer. Documentation of activities is carried out in the form of photos of activities and reports which are one of the evidence of the implementation that has been carried out The conclusion that the service activities providing training on monitoring blood glucose levels in DM patients with a glucometer device who are self-isolating members of Persadia Semarang an increase knowledge so that patients practice at home.Keywords: checks blood glucose, PERSADIA, training